Mild Pre Eclampsia (Garbhini Shotha) in Pregnancy - A Correlational Review (AYUSHDHARA, 2022)
Pregnancy in the life of a female is like a beautiful chapter that provides a purpose of living and makes her a complete woman simultaneously. Every female has a beautiful story of their own in their pregnancy which they cherish throughout their lifetime and nobody wants it to be life threatening. Earlier majority of the women were undergoing only the normal delivery due to their food habits and lifestyle practices. Presently C-section has dominated due to modern lifestyle practices, dietary habits and most important stress as the causative factor for the complications of pregnancy. Pre eclampsia being one of the commonest complications during pregnancy is leading to severe morbidity and mortality. Various treatment methods are being followed for the prevention of the same in different systems of medicine. Present study was made to elucidate an in-depth literature of pre eclampsia in ancient system of medicine called Ayurvedic science and to find the possible methods to manage the health issue. Based on the available Ayurvedic literature and the Modern, Pre eclampsia can be correlated to Garbhini Shotha based on the signs and symptoms including various treatment methods.